2017
DOI: 10.1007/s00423-017-1553-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative controlling nutritional status (CONUT) is useful to estimate the prognosis after esophagectomy for esophageal cancer

Abstract: CONUT is convenient and useful for preoperatively assessing malnutrition and prognosis of esophageal cancer patients who underwent surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 37 publications
0
48
1
Order By: Relevance
“…Recently, the prognostic value of the preoperative CONUT score has been reported in many types of malignancies, such as colorectal cancer, esophageal cancer, gastric cancer, and renal cell carcinoma. [14][15][16][17] However, there are few studies on UTUC. Shihara and Xu reported that the CONUT score is an independent prognostic factor in UTUC patients treated with surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the prognostic value of the preoperative CONUT score has been reported in many types of malignancies, such as colorectal cancer, esophageal cancer, gastric cancer, and renal cell carcinoma. [14][15][16][17] However, there are few studies on UTUC. Shihara and Xu reported that the CONUT score is an independent prognostic factor in UTUC patients treated with surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative dysphagia, due to obstruction by tumor, and esophagectomy could cause malnutrition and weight loss in esophageal cancer patients. [ 9 , 10 ] Preoperative malnutrition and reduced skeletal muscle volume, that is, presarcopenia, are reportedly associated with a higher frequency of postoperative complications and worse short-term outcomes. [ 9 ] However, it remains unclear whether nutritional alterations following esophagectomy affect long-term pneumonia-related morbidity and long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, EC patients have a high risk of being malnourished prior to treatment, and there is accumulating evidence demonstrating that poor nutritional status is associated with inferior clinical prognosis in patients who underwent esophagectomy. 6 8 Therefore, pretreatment nutritional condition is important for the prognosis of ESCC in patients receiving surgery. At present, there are many assessment methods applied to nutritional evaluation; 9 11 among these, Nutritional Risk Screening 2002 (NRS-2002) was a new evaluation system, published by the European Society for Clinical Nutrition and Metabolism (ESPEN) in 2002 and was based on 128 randomized controlled trials.…”
Section: Introductionmentioning
confidence: 99%